GEOLOGICAL AND GEOTECHNICAL CHARACTERISTICS OF THE SOILS IN THE REGION OF SÉTIF - Djenba Samir (European Scientific Journal, ESJ, 2013)
Given its strategic location, the wilaya of Setif is the crossroads between the IS and the center of one side and the coastal towns of South and other side. it occupies the second round of a national demographic point of view and a large socioeconomic pole, hence the expansion into new land for urban or industrial activities or for the inevitable. The majorises of this expansion is focused on the meridian Sétif El Eulma due to the topography and other predisposing infrastructure already interesting recently reinforced by the East-West. Several geotechnical studies have been done on this area has been chosen four different sites geographically distant to characterize these deposits. Éternitaire three sites on the east-west highway, it is the points of interchanges and toll point Near the town of El eulma and agglomeration Ain sfiga and near the town of Ain Arnet, the fourth site is the foundation of a wastewater treatment plant Bazer Sakhra. The approach in this study is geological soil description of Setif, we also tested through several geotechnical brought to the region, to characterize these soils by hand is an in situ testing and secondly by testing the laboratory. This study has shown that the Setif high plains generally consist of deposits by fluviolacustres Mioplioquaternaire age, are from top to bottom of arable brown silty clays, limestone crusts villafranchiennes and red clay. Geotechnical data have shown that the soils are classified into two categories: O 2 meters sand gravel BC, inferior to 2 meters considered stiff clays Class B.